Representaciones Sociales de Cuatro Mujeres Deportistas de Alto Rendimiento Sobre La Feminidad (2015)
The following document has as a target to describe the social representations about femininity in women who are high performance athletes who belong to the League of Bogota in their respective sports, was made from a qualitative methodology, using life stories as a method of data collection, these were analyzed from the theory of social representations. As a result regarding the participants even though each has different contexts, in the story of life, emerge variety of opinions, in which some coincide including, as differences arising between themselves, but also in couples Flower Shops match or not in some way.